The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/tax.616007
|View full text |Cite
|
Sign up to set email alerts
|

Delimitation of the genus Margaritopsis (Rubiaceae) in the Asian, Australasian and Pacific region, based on molecular phylogenetic inference and morphology

Abstract: In the past, the circumscription of the large genus Psychotria (Rubiaceae) was difficult, until molecular phylogenetic studies revealed its considerable paraphyly, enabling the delimitation of its major lineages and the grouping of related genera, and most notably the separation of Psychotria and its relatives (former Psychotrieae) into two tribes: Psychotrieae and Palicoureeae. The genus Margaritopsis, which is included in Palicoureeae, encompasses 27 Neotropical species, and in previous studies these have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 61 publications
2
34
0
1
Order By: Relevance
“…More genera (at least thirteen) show evidence of polyphyly or paraphyly in the Society Islands than strongly supported monophyly (four; Table ). Some of polyphyletic/paraphyletic groups are best interpreted as repeated independent colonizations of the Societies from elsewhere: these include the forest herbs Peperomia (Piperaceae; Bradley, ), the understorey shrubs Cyrtandra (Gesneriaceae; Clark et al ., ), Psychotria (Rubiaceae; Barrabé et al ., , ) and Melicope (Rutaceae; Meyer et al ., ), succineid snails (Holland & Cowie, ), Tetragnatha spiders (Gillespie, ; Gillespie et al ., ; Casquet et al ., ), Epicephala moths (leafflower moths; Hembry et al ., ) and kingfishers (the Chattering Kingfisher Todiramphus tutus and the Society Kingfisher T. veneratus ; Andersen et al ., ). Peperomia , Cyrtandra , Melicope , Epicephala , Tetragnatha and Succineidae all show evidence of the repeated colonization of the same island (Table ).…”
Section: Polyphyly Of Societies Taxa (Multiple Colonizations or Sociementioning
confidence: 99%
“…More genera (at least thirteen) show evidence of polyphyly or paraphyly in the Society Islands than strongly supported monophyly (four; Table ). Some of polyphyletic/paraphyletic groups are best interpreted as repeated independent colonizations of the Societies from elsewhere: these include the forest herbs Peperomia (Piperaceae; Bradley, ), the understorey shrubs Cyrtandra (Gesneriaceae; Clark et al ., ), Psychotria (Rubiaceae; Barrabé et al ., , ) and Melicope (Rutaceae; Meyer et al ., ), succineid snails (Holland & Cowie, ), Tetragnatha spiders (Gillespie, ; Gillespie et al ., ; Casquet et al ., ), Epicephala moths (leafflower moths; Hembry et al ., ) and kingfishers (the Chattering Kingfisher Todiramphus tutus and the Society Kingfisher T. veneratus ; Andersen et al ., ). Peperomia , Cyrtandra , Melicope , Epicephala , Tetragnatha and Succineidae all show evidence of the repeated colonization of the same island (Table ).…”
Section: Polyphyly Of Societies Taxa (Multiple Colonizations or Sociementioning
confidence: 99%
“…It encompasses more than 55 species . As mentioned above, three of them were recently separated from this genus to form the Margaritopsis genus . These three species were analyzed and it was showed that these contain alkaloids.…”
Section: Asteridsmentioning
confidence: 99%
“…They concluded that alkaloid‐bearing plants seem to be restricted to the genera Guettarda , Gea , Tinadendron , Psydrax , Augusta , Coelospermum , and ‘Psychotria ’. Recently, the phylogeny of New Caledonian Psychotria species have been revised and are now separated into two genera, namely Margaritopsis and Psychotria . All species which have been investigated so far belong to Margaretopsis genus.…”
Section: Asteridsmentioning
confidence: 99%
See 2 more Smart Citations